Communities of kinship: retrieving Christian practices of solidarity with lepers as a paradigm for overcoming exclusion of older people - Calleja, Carlo (Lexington Books/Fortress Academic, 2024)
"Finding parallels between the exclusion of lepers and the efforts of Christian communities to reforge kinship bonds with them in ancient and medieval times, Carlo Calleja argues that communities of kinship with older persons can help cultivate the virtues needed for the flourishing of oneself and society"--